(untitled) - Hegel, Georg Wilhelm Friedrich (Cambridge, 1980)
In the introduction to his lectures, Hegel lays down the principles and aims which underlie his philosophy of history, and provides an outline of the philosophy of history itself. The comprehensive and voluminous survey of world history which followed the introduction in the original lectures is of less interest to students of Hegel's thought than the introduction, and is therefore not included in this volume.
Keywords: History,Lịch sử; Philosophy,Triết học